2014
DOI: 10.1111/2049-632x.12173
|View full text |Cite
|
Sign up to set email alerts
|

Oral immunization with recombinantLactococcus lactisdelivering a multi-epitope antigen CTB-UE attenuatesHelicobacter pyloriinfection in mice

Abstract: Urease is an essential virulence factor and colonization factor for Helicobacter pylori (H. pylori) and is considered as an excellent vaccine candidate antigen. However, conventional technologies for preparing an injectable vaccine require purification of the antigenic protein and preparation of an adjuvant. Lactococcus lactis NZ9000 (L. lactis) could serve as an antigen-delivering vehicle for the development of edible vaccine. In previous study, we constructed a multi-epitope vaccine, designated CTB-UE, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…For this reason, different routes of administration were examined. For example, in the case of S. pneumoniae , the efficacy of intranasally administered vaccines was evaluated (Hanniffy et al 2007 ), whereas in the case of Helicobacter pylori , oral or intragastric vaccines were the first to be analyzed (Li et al 2014 ). Because the mucosa-associated lymphoid tissue (MALT) mucous-membrane immune system constitutes one network covering the whole body, and because lymphocytes are able to migrate, oral immunization also provides systemic immunity expressed by the mucous membranes of other organs.…”
Section: Lab As Carriers Of Heterologous Bacterial Parasitic and VImentioning
confidence: 99%
“…For this reason, different routes of administration were examined. For example, in the case of S. pneumoniae , the efficacy of intranasally administered vaccines was evaluated (Hanniffy et al 2007 ), whereas in the case of Helicobacter pylori , oral or intragastric vaccines were the first to be analyzed (Li et al 2014 ). Because the mucosa-associated lymphoid tissue (MALT) mucous-membrane immune system constitutes one network covering the whole body, and because lymphocytes are able to migrate, oral immunization also provides systemic immunity expressed by the mucous membranes of other organs.…”
Section: Lab As Carriers Of Heterologous Bacterial Parasitic and VImentioning
confidence: 99%
“…In this sense, poor immune responses reported by some groups using live L . lactis have been attributed to the low amount of the expressed antigen in this system [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…They showed that passive immunization of 6 days old chicks with IgY obtained from egg yolks of hens immunized with C. jejuni lysates or fraction of C. jejuni hydrophobic proteins resulted not only in reduction their colonization by homologous C. jejuni strain but also reduce the pathogen transmission to not infected birds ( Hermans et al, 2014 ). More and more LAB, mainly members of the Lactococcus and Lactobacillus genera, have been tested as vehicles for the delivery of heterologous bacterial or viral antigens into animal mucosal immune systems ( Marelli et al, 2011 ; Villena et al, 2011 ; Kajikawa et al, 2012 ; Fontana et al, 2013 ; Li et al, 2014 ). In this work, we employed L. lactis because genetic engineering tools for this bacterium have been worked out in detail ( Fontana et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%